Peran penyuluh pertanian dalam usahatani kelapa sawit di Desa Sabbang, Kecamatan Sabbang, Kabupaten Luwu Utara - Sumantri Sumantri; Ratna Ratna (Jurnal Agercolere, 2019)
This study aims to determine the role of agricultural extension workers in oil palm farming in Sabbang Village, Sabbang District, North Luwu Regency. This research was conducted in January 2019 with the number of farmers being sampled as many as 31 respondents. Data collected in the form of primary data with secondary data, while the method of collecting data through interviews and observation. The analytical method used is descriptive statistics using a Likert scale. The results showed that the role of agricultural instructors in oil palm farming in Sabbang Village as a whole can be categorized as quite well with a score of 91.76 in carrying out their duties and functions. The role of the agriculture instructor in carrying out education is categorized very well with a score of 108.2, The role of the agricultural instructor in carrying out facilitation is categorized not good with a score of 77, The role of the agriculture instructor in conducting consultations is categorized as quite well with a score of 96, with a score of 81.4, the role of agricultural extension agents in carrying out monitoring and evaluation is categorized as quite well with a score of 96.2.